Oncogenic PIK3CA corrupts growth factor signaling specificity - Ralitsa R Madsen; Alix Le Marois; Oliwia N Mruk; Margaritis Voliotis; Shaozhen Yin; Jahangir Sufi; Xiao Qin; Salome J Zhao; Julia Gorczynska; Daniele Morelli; Lindsay Davidson; Erik Sahai; et al. (Molecular Systems Biology)
Abstract Technical limitations have prevented understanding of how growth factor signals are encoded in distinct activity patterns of the phosphoinositide 3-kinase (PI3K)/AKT pathway, and how this is altered by oncogenic pathway mutations. We introduce a kinetic, single-cell framework for precise calculations of PI3K-specific information transfer for different growth factors. This features live-cell imaging of PI3K/AKT activity reporters and multiplexed CyTOF measurements of PI3K/AKT and RAS/ERK signaling markers over time. Using this framework, we found that the PIK3CA H1047R oncogene was not a simple, constitutive activator of the pathway as often presented. Dose-dependent expression of PIK3CA H1047R in human cervical cancer and induced pluripotent stem cells corrupted the fidelity of growth factor-induced information transfer, with preferential amplification of epidermal growth factor receptor (EGFR) signaling responses compared to insulin-like growth factor 1 (IGF1) and insulin receptor signaling. PIK3CA H1047R did not only shift these responses to a higher mean but also enhanced signaling heterogeneity. We conclude that oncogenic PIK3CA H1047R corrupts information transfer in a growth factor-dependent manner and suggest new opportunities for tuning of receptor-specific PI3K pathway outputs for therapeutic benefit.